Hydrochemical evaluation of the quality of some Brazilian waters - Bonotto, Daniel Marcos [UNESP] (2008)
This investigation was carried out within the Parane sedimentary basin and neighbourhood in Brazil and involved the sampling of different water types with the purpose of evaluating its quality. Several methods were utilized for acquiring the hydrochemical data and a novel technique has been developed for evaluating the gross alpha and beta radioactivities in water, through a combined gamma-alpha spectrometry technique. The results obtained for the analyzed samples were compared with the guideline values established by the São Paulo State and Brazilian Health Ministry legislations for defining potable water standards and for the prevention and control of pollution in the environment. The hydrochemical data allowed evaluation of diverse problems related to the interaction between society and the environment such as sugarcane production and the releases associated with gas stations suppliers. The geogenic input of sulfate in groundwater was also identified. The established radiometric technique was properly calibrated and successfully applied to the analysis of different water types utilized for human consumption.